Moderasi Beragama Era Rasulullah: Pembacaan Ulang Konsep Tanah Suci Madinah Dalam Perjanjian Hudaibiyah - Yeni Yeni; Abbas Sofwan Matlail Fajar (UIN Syarif Hidayatullah Jakarta, 2022)
Religious moderation for Muslims is a necessity. The practice of religious moderation has even been carried out since the time of the Prophet. The Apostle is not extreme and does not fully allow religion. For example in the commitment to nationality, the Prophet has set an example through the Medina Charter he made. Even though the term nationality did not exist at the time of the Apostle because this term was a new term that emerged in the modern era. Moderation of Islam as an object of scientific study is considered important to continue to be developed and prioritized for the community. This is because a mature and quality understanding of Islamic moderation is seen as very influential on diversity and socio-cultural life. The concept of the holy land of Medina in the hudaibiyah agreement. Hudaibiyah is a city located about 26 kilometers from the Grand Mosque. Currently, the area is also known as the border area of the Haram Land, so it is often used as a miqat for Muslims who perform the pilgrimage or umrah. The name Hudaibiyah is actually taken from the name of the lake which is also known as the Asy-Syumaisi lake. Islamic history mentions, Hudaibiyah became the entrance to the brilliance of Muslims in conquering the City of Makkah (Fathul Makkah). This article is an article written by the author who refers to Religious Moderation in the Prophet's Era: Rereading the Concept of the Holy Land of Medina in the Hudaibiyah Agreement which explains moderation and reviews the concept of hubaidiyah agreements that existed at the time of the Prophet Muhammad. The purpose of writing this article is to find out about religious moderation in the Prophet's Era: Rereading the Concept of the Holy Land of Medina in the Hudaibiyah Agreement. The research method used by the author is a qualitative literature study, which uses descriptive methods, interpretive analysis of the text of the story of the apostles. By using the constructive comparative argumentative method, this research uses various sources of literature, such as books, journal articles, and dissemination on website pages. Religious Moderation in the Prophet's Era: Re-reading the concept of the Holy Land of Medina in the Hudaibiyah Agreement which can be seen from several aspects, namely the Traces of Moderation, Religious Moderation in Islamic Education as outlined in a book entitled